Correlatos cognitivos da habilidade de leitura e escrita de jovens e adultos brasileiros pouco escolarizados - Marcela Fulanete Correa (2013)
The purpose of this study was to evaluate the independent contribution of phonological awareness and rapid serial naming to reading and spelling abilities of youth and adults with low literacy skills. In contrast to what has been done with children, the contribution of these cognitive skills to reading and spelling acquisition by young and adults has received less attention from researchers. Two empirical studies were conducted to attend this objective. In the first study, the relative contribution of phonological awareness and rapid serial naming was evaluated in a sample of 72 youth and adults enrolled in a literacy acquisition program. The results indicated that although phonological awareness and rapid serial naming have contributed significantly and independently to reading accuracy, just phonological awareness explained the variations in spelling. In the second study, 100 youth and adults enrolled in advanced phases of education programs were included in the sample. The results indicated that phonological awareness was a significant predictor of word reading and spelling accuracy, while rapid serial naming was strongly associated with word and nonword reading fluency. Together, these findings extend those found among children and indicate that phonological awareness and rapid serial naming are two important sources of variation in reading and spelling acquisition by young and adults.These results, however, question (1) the hypothesis that rapid serial naming are more important than phonological awareness to reading and spelling acquisition in orthography characterized by consistent letter-sound relations, and (2) the hypothesis that rapid serial naming contributes more than phonological awareness for orthographic coding. This work also aimed to examine the development of orthographic skills in adults with different levels of education. To this end, a new empirical study was conducted. This study included 26 adults at the beginning phases of a literacy program and 26 children individually matched with the adults for the ability to read words. The study also included 79 adults enrolled in more advanced literacy classes and 79 children with the same reading level. Results indicated that, similar to children, adults are sensitive to grapho-phonological patterns in words from the beginning of literacy acquisition. On the other hand, they are less sensitive to morphosyntactic orthographic rules than children of the same reading level.